Stealth construction : integrating practices for resilience and sustainability - Stephen, Seyi S.; Oke, Ayodeji E.; Aigbavboa, Clinton Ohis; Akinradewo, Opeoluwa I.; Adetoro, Pelumi E.; Ikuabe, Matthew (Emerald Publishing Limited, 2025)
Historically known for its significant environmental footprint, the construction industry faces increasing pressure to evolve in a landscape where environmental concerns, resource efficiency, and adaptability are paramount. Stealth Construction explores a strategic amalgamation of diverse construction practices and technologies into resilient construction with the aim of improving construction environmental protection, safety, speed (project delivery), economy, and aesthetics. A pivotal publication at the nexus of construction innovation, the book empowers its readers to adapt to the changing landscape and contribute to shaping a more resilient and sustainable built environment.
Includes index.
Keywords: Sustainable buildings.; Technology & Engineering -- Construction -- General.; Building construction and materials.; Building skills and trades.; elektronické knihy; electronic books